PENGARUH PEMBELAJARAN BERBASIS TEKNOLOGI TERHADAP EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA SISWA DI SMK NEGERI 3 TELUK KUANTAN - Ade Muria; Sopiatun Nahwiyah; Andrizal Andrizal (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
This research is based on the existence of Islamic Religious Education Teachers who apply technology-based learning. This can be seen from the teacher's activities when delivering subject matter using information technology media. The teacher designs the learning material by involving information technology media, and the teacher presents the material using information technology media such as an infocus, laptop and Flasdisc which contains learning programs for example Tajwid and Jenazah Prayers. However, the facts that occur in the learning process of Islamic Religious Education are still not effective. This problem can be seen from the following symptoms: (1) Communication that occurs in the learning process of Islamic Religious Education runs only in one direction, namely from teacher to student only, while from student to teacher and from other students there is less communication; (2) There are still students who are not active in the learning process, such as not wanting to ask the teacher and just keep quiet when discussing; (3) There are still students who do not focus their attention on the subject matter delivered by the teacher but students are busy paying attention to other things outside the subject matter, such as chatting with their classmates; (4) There are still students who refuse when the teacher asks students to come to the front of the class to practice the material that has been explained by the teacher.Based on the results of the analysis, the research can be concluded as follows: (1) Learning based on technology at SMK Negeri 3 TelukKuantan by 65.8% is categorized as Good; (2) The effectiveness of Islamic religious education at SMK Negeri 3 TelukKuantan is 31.6% categorized as Less effective; (3) There is a significant effect of technology-based learning on the effectiveness of Islamic Religious Education learning for students at SMK Negeri 3 TelukKuantan, because the price rcount (0.533) ≥ rtable 5% (0.325) and 1% (0.418). From the results of interpretation, the correlation coefficient shows the level of influence of the two variables in the "Strong Enough" category. The contribution of technology-based learning variables to the learning effectiveness variable of Islamic Religious Education for students at SMK Negeri 3 TelukKuantan was 28.4%. While the remaining 71.6% is contributed by other variables which are not discussed in this study.